An endoplasmic reticulum targeting green fluorescent protein chromophore-based probe for the detection of viscosity. Issue 76 (7th September 2022) - Wei, Xiaoqin; Zhu, Yiming; Yu, Xiang; Cai, Lei; Ruan, Nanan; Wu, Luling; Jia, Nengqin; James, Tony D.; Huang, Chusen
Abstract : The occurrence of endoplasmic reticulum (ER) stress is the main cause of a variety of biological processes that are closely related to numerous diseases. Abstract : The occurrence of endoplasmic reticulum (ER) stress is the main cause of a variety of biological processes that are closely related to numerous diseases. The homeostasis of the ER microenvironment can be disrupted under ER stress. In this research, by linking a pentafluorophenyl to the green fluorescent protein chromophore, we have developed a new ER-targeting fluorescent probe (GE-Y ) for measuring changes of intracellular ER viscosity caused by ER stress. Importantly, an increase in ER viscosity was observed using GE-Y in cells undergoing autophagy. As such, our research provides an ideal tool for studying ER stress and autophagy.